(untitled) (Interdisciplinary Research in Education, 2023)
The objective of this study is to find out the major problems and concerns of teachers in teacher education. This is a literature review based study. The descriptive method was employed in this study. The goal of a program called "teacher education" is to help educators become more effective and competent so they can fulfill the demands of their jobs and the problems posed by globalization. We must try to improve our teacher preparation program if we want to have good teachers. The findings indicate that teachers in Nepal confront a number of difficulties in their line of work. It was found that traditional curricula, a lack of developing creativity, life skills, and a lack of training in teaching skills, and traditional teaching strategies, low school supervision, insufficient empirical research, profit-oriented education, a lack of ICT-based teaching and learning, etc. are the main issues and problems in teacher education. Additionally, there is a serious issue due to the imbalance between the supply and demand for teachers. To improve the standard of teacher education, it is crucial to empower teachers to perform well. The corrective actions to enhance teacher education include proper scheduling and use of human resources, management of qualified staff, provision of adequate facilities and equipment, appropriate techniques, effective teaching practices, quality improvement, research skills, changes in the role of teachers, integration of ICT in teacher education, and other things. However, effective action should be taken by the central and local governments to strengthen the programs for teacher education.